0605 Sodium Oxybate Dosing Utilization Patterns in the Nexus Narcolepsy Registry. (12th April 2019) - Ohayon, Maurice M; Thorpy, Michael J; Short, Sarah A; Williams, Michael J; Yang, Mo; Black, Jed; Hyman, Danielle L; Profant, Judi; Villa, Kathleen F
Abstract: Introduction: The recommended dosage range for sodium oxybate (SXB) among adults with narcolepsy is 6-9g per night orally, divided into 2 equal doses. The objective of this study was to describe real-world dosing of SXB among adults with narcolepsy. Methods: The Nexus Narcolepsy Registry is an ongoing, self-reported online registry of adults diagnosed with narcolepsy. The study identified SXB users who had reported dosage data and compared those currently taking SXB vs those who previously discontinued. Of current users, those taking SXB <3 months (hereafter "new users") vs ≥3 months (hereafter "established users") also were compared. The survey assessed once-nightly or twice-nightly SXB dosing across the dose range (<4.5g, 4.5-<6g, 6-<9g, 9g, >9g), and equally-divided (1st dose=2nd dose) vs asymmetric dosing (1st dose≠2nd dose). Descriptive analyses and t tests assessed sample characteristics and dosing patterns. All P values are uncontrolled for multiplicity, hence, are nominal. Results: Among all participants reporting SXB use (n=365), 65% were current users and 95% took SXB twice nightly. Average total nightly dose (standard deviation) was 7g (±1.9) and 3.6g (±0.9) for twice-nightly and once-nightly dosing, respectively. Among those who took SXB twice nightly, the total nightly dose was lower in those who discontinued vs current users (5.9g ±2.1 vs 7.6g ±1.6; P <0.001) and lower in new users vs established users (6.5g ±1.8 vs 7.7g ±1.5; P <0.001). Among all SXB users, 66% reported doses within the recommended dosage range of 6-9g per night; 80% of current users and 40% of discontinued users took 6-9g per night. Nearly 30% of all SXB users, 16% of current users, and 55% of discontinued users took <6g per night. Among all SXB users, 84% reported equally-divided dosing. For current new users and current established users, 96% and 83%, respectively, reported equally-divided dosing. Conclusion: Among SXB users in the Nexus Narcolepsy Registry, the majority reported taking SXB twice nightly, with the total nightly dose equally divided. 17% of current established users reported asymmetric dosing, and 5% of all SXB users reported once-nightly dosing. Support (If Any): Jazz Pharmaceuticals